An exploratory study on Vietnamese university students’ resilience in learning English as a foreign language - Lap, Trinh Quoc; Trang, Vo Thi Thuy; Tuan, Le Cong (Frontiers in Education, 2025)
Learning a second language (L2) is believed to be a long process with various challenges. While many students tend to give up or fall behind when faced with difficulties, others can overcome them to learn even better. It has been acknowledged that this is associated with academic resilience, the ability to cope with and adapt to adversity in learning. Realizing the importance of this capability, the current study aimed to investigate the level of academic resilience among English majors at a university in the Mekong Delta region. In addition, the potential difference between male and female students was explored. The study attempted to identify frequent obstacles and coping strategies among the study’s participants. A total of 150 English majors were involved in the research survey, and five were chosen to participate in the interviews. The findings revealed that the participants have an average degree of resilience, and there is no difference in terms of gender in their levels of resilience. The students’ struggles mainly stemmed from linguistics-related challenges, high teacher and curriculum demands, individual shortcomings, and demotivation factors. However, the students suggested several helpful strategies to deal with the difficulties and move toward becoming more resilient learners.